Austic Spectrum Disorders in the Early Years. - Plimley, Lynn (Autistic Spectrum Disorder Support Kit., 2007)
Looking at the early years of a child's life, this book provides information on the services that are available for those from birth to five years, and addresses issues related to identification, assessment, teaching and learning and family support. It is illustrated with case studies provided by parents and practitioners, and discusses: o the Code of Practice for SEN & the SEN and Disability Discrimination Act. o identification and assessment. o good practice examples of multi-agency collaboration and provision. o partnership with parents. o social skills and behaviour. o alternative interven.